From Jim Crow to civil rights : the Supreme Court and the struggle for racial equality - Klarman, Michael J. (Oxford University Press, 2004)
Publisher's description: Do Supreme Court decisions matter? In this book, Michale J. Klarman examines the social and political impact of the Supreme Court's decisions involving race relations from Plessy, the Progressive Era, and the Interwar period to World Wars I and II, Brown and the Civil Rights Movement. He explores the wide variety of consequences that Brown may have had - raising the salience of race issues, educating opinion, mobilising supporters, energising opponents of racial change. He concludes that Brown was ultimately more important for mobilising southern white opposition to radical change than for encouraging direct-action protest.